2008
DOI: 10.1021/ac7019915
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescent Immunoassays on Silver Fractal-like Structures

Abstract: Using the effect of the fluorescence enhancement in close proximity to metal nanostructures, we have been able to demonstrate ultrasensitive immunoassays suitable for the detection of biomarkers. Silver fractal-like structures have been grown by electrochemical reduction of silver on the surface of glass slides. A model immunoassay was performed on the slide surface with rabbit IgG (antigen) noncovalently immobilized on the slide, and rhodamine red-X-labeled antirabbit IgG conjugate was subsequently bound to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
0
53
0
Order By: Relevance
“…Tanya Shtoyko observed significant fluorescence enhancement signal from the silver fractals nanostructure, when fabricated using the electrochemical reduction method. He found that the fluorescence enhancement effect is critically dependent on the topography and dielectric properties of fabricated sample [70]. Due to the LSPR, the more the "hotspots" in the fractal-like nanostructure, the stronger EF will be obtained.…”
Section: Pef From Metallic Fractal-like Substratementioning
confidence: 99%
“…Tanya Shtoyko observed significant fluorescence enhancement signal from the silver fractals nanostructure, when fabricated using the electrochemical reduction method. He found that the fluorescence enhancement effect is critically dependent on the topography and dielectric properties of fabricated sample [70]. Due to the LSPR, the more the "hotspots" in the fractal-like nanostructure, the stronger EF will be obtained.…”
Section: Pef From Metallic Fractal-like Substratementioning
confidence: 99%
“…Among the most notable of these are nanotriangle arrays or bowties 151,153,154 and silver fractals (fabricated via electrochemical growth). 155 In each of these cases, the resulting plasmonic nanostructures resulted in significantly greater MEF enhancements than silver island films for the particular fluorophores employed. …”
Section: Traditional Metal-enhanced Fluorescence Nanostructures For Smentioning
confidence: 99%
“…[3][4][5][6][7][8] Fluorescence enhancement based on the localized surface plasmon resonance of a silver island structure is well known as a typical fluorescence enhancement technique. Such a structure can improve the sensitivity of target detection up to approximately 50-fold compared with that of a flat control surface.…”
Section: Introductionmentioning
confidence: 99%